EKOLOGI KONSTITUSIONAL (GREEN CONSTUTIONAL) DAN KEDAULATAN WILAYAH DI INDONESIA - Jawade Hafidz (Jurnal Hukum, 2011)
Green Constitusional is a concept contained in the Act of 1945 Amendments, which in Article 33 Paragraph (3) arranged on the environment that must be managed for the benefit of development based on sustainable principles (suistainable) and environment (pro-enviroment). Green Constitusional concept first introduced by Jimly Asshiddiqie the first time in which this is one of the ideas and developments in environmental protection efforts are put towards environmental rights arrangements in the constitution of the State as a commitment to environmental protection and management.Constitution of the Republic of Indonesia 1945 Amendments also referred to as the supreme law of the land, because in its articles have known or regulating the preservation of nature or has shades of green. This is also confirmed in the Constitutional Court Decision No. 013/PUU-III/2005 dated 12 September 2005 that the politics of Indonesia's forest is in the implementation of human rights in Indonesia today and future generations to gain a healthy environment and in order implementation of national development.Key Word : Ecological Constitution, Sovereignty, Indonesia